Fantasies of Fragmentation in Conrad, Kafka and Pessoa: Literary Strategies to Express Strangeness in a Hetero-social Context - Bär, Gerald (Amaltea. Revista de Mitocrítica, 2011)
Many authors, such as Chamisso, Conrad, Rilke, Kafka, Pessoa, Goll, Nabokov, Celan and Beckett grew up bi- or multilingual, or lived in linguistically and culturally hybrid regions. Recurring to examples of texts by Joseph Conrad, Franz Kafka and Fernando Pessoa, this paper focuses on their common tendency of developing new concepts of the self, by exploring the frontiers of alterity. In a social context, which is often experienced as threatening, the strangeness of being of their literary characters, often expresses itself in a double- or hetero-social consciousness, articulated in the same narrative. In this creative process, fantasies of fragmentation take the shape of doppelgangers, heteronyms, animals and even insects. The following article is a revised version of the paper presented at the Annual Meeting of the American Educational Research Association (AERA), Denver, Col., 3 May 2010.